Occupational therapeutic recreation in the elderly as a strategy to prevent cognitive impairment - Arias Silva, Cecilia Fernanda; Mena Garzón, Narcisa de Jesús; Cabezas Mejía, Edison Damián (mktDESCUBRE; Vol 1 No 19 (2022): Nineteenth Edition (January - June), 2022)
Cognitive impairment is a geriatric syndrome that commonly occurs after 65 years of age, currently there are alternatives to counteract this syndrome; The objective of this research is: To establish the incidence of occupational therapeutic recreation as a tool to prevent cognitive deterioration in the elderly of the Sagrada Familia Residential Gerontological Center of the canton of La Maná, Province of Cotopaxi. The methodology used was based on a mixed approach, with documentary, field and quasi-experimental designs; To collect data, documentary analysis techniques and standardized instruments such as the Folstein Mini Mental State Examination (MMSE) were used. As a result of the application of the MMSE, it is observed that 100% of older adults present, according to the scale, a mild cognitive impairment, for which a therapeutic recreational program is proposed, evidencing a significant improvement; a change of scale from mild cognitive to a pathological suspicion in 28% and in the same way from mild cognitive to a normal condition in 8%. The therapeutic recreational program decreased cognitive deterioration in the elderly according to inferential statistical information.